Content validity and exploratory factor analysis (EFA) on 26 items of the interreligious harmony scale. - Permadi, Aad Satria; Ismail, Rozmi; Kasim, Arena Bt. Che (Universitas Muhammadiyah Surakarta, 2022)
Abstract. A qualitative study in Waingapu revealed five factors that form interreligious harmony: belief in one ancestor, religious dogma, respect, perception of interreligious incidents, and internal attribution. This study aimed to test the content validity and EFA of 26 items compiled based on these five factors. Content validity was carried out by querying an assessment from 18 raters using the Aiken's V formula. Five hundred fourteen respondents fill out the scale of interreligious harmony. The data from 514 respondents were then processed with the JASP for Windows 10 program. All items obtained Aiken's V values 0.65. The Aiken's V value means that the items are valid in terms of their content. Overall MSA value was 0.610, and Bartlett's test p-value was 0.001. The EFA calculation result in seven items that were aggregated in two factors with a loading factor was 0.4. The EFA calculation shows that the seven items that constructed these two factors are valid for measuring the theoretical construct of Interreligious Harmony. The difference between theoretical factors and those formed after EFA is also discussed in this article as well.Keywords: content validity; confirmatory factor analysis; interreligious harmony